D-Optimal Design Optimization for the Separation of Oleic Acid from Malaysian High Free Fatty Acid Crude Palm Oil Fatty Acids Mixture Using Urea Complex Fractionation - Bahadi, Murad; Salih, Nadia; Salimon, Jumat (Applied Science and Engineering Progress, 2021)
Oleic acid (OA) rich vegetable oils is important for the daily essential dietary oils intake but restrict to particular oil such as olive oil. However OA enrichment to other vegetable oil such as palm oil is always possible. OA can be obtained from cheap resources such as high free fatty acid crude palm oil (HFFA-CPO). OA concentrate from HFFA-CPO fatty acids mixture requires efficient and low cost technique. Urea complex crystallization fractionation is a classic method for fractionating saturated and monounsaturated fatty acids from polyunsaturated fatty acids of many vegetable oils. In this work, the separation and purification of oleic acid (OA) from unsaturated fatty acids mixture fraction (USFA) of HFFA-CPO fatty acids mixture by urea complex fractionation (UCF) was studied. The crystallization reaction conditions of urea inclusion for the non-urea complex fraction (NUCF) were optimized using the response surface methodology (RSM) and the optimal model was developed. The results showed high content of OA (88%) in urea complex fraction (UCF) with 86% yield at optimal conditions of urea-to-USFAs ratio of 4.62 : 1 (w/w), crystallization temperature at –10°C and crystallization time of 24 h. The results have demonstrated that urea complex crystallization fractionation method is a very effective with low cost, stable, obtainable, and comparatively ease to recover of OA from polyunsaturated fatty acids (PUFA) of an oil fatty acids mixture. Pure OA is plausible to be used back for the OA enrichment modification into palm oil for new dietary oil.